The management motives in analysing accounting misstatements of Malaysian public listed companies (PLCs) - Mohamed Hussain, Alfiatul Rohmah; Mohd Sanusi, Zuraidah; Mahenthiran, Sakthi; Hasnan, Suhaily (2015)
This paper discusses issues concerning management motives and situational pressures that lead to financial reporting misstatements.The situational pressures and management motives are measured using financial distress, family ownership, founders on board and earnings management of Malaysian public listed firms (referred to as PLCs) that influence the occurrence of accounting misstatements.Results show that founder on board (FOUNDER) is positively significant while family ownership (FAMOWN) is negatively significant determinants of the accounting misstatement proxy financial statement restatements.Two other variables namely financial distress (DISTRESS) and earnings management (EM) interact significantly and positively to affect accounting misstatements. Additionally, family ownership interacts with EM to positively affect accounting misstatements. Findings reveal that the extent of earnings management and financial distress and family-ownership of affect the likelihood of financial statement restatements by Malaysian PLCs.